Convalescent Plasma Therapy: a Possible Treatment of COVID-19 Pandemic - Sapkota, Shubha Devi; Sharma, Monika; Bhusal, Gehendra (Europasian Journal of Medical Sciences, 2020)
COVID 19 is a newly recognized infectious disease that has rapidly spread with no verified treatment available. It is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2). In Convalescent plasma therapy, the yellowish liquid or the plasma from the recovered blood is used to treat the patient suffering from the same illness. For more than 100 years it has been used to treat severe infections with varying degrees of success. For this present infection, multiple clinical trials on plasma therapy are still under vigorous investigation. Despite the very low chance of risks like allergies, lung damage, and transmission of blood-related infection, the therapy has shown a positive result in the recovery of the patients. Many experts are observing its use as a “stopgap measure” until effective vaccines and antiviral drugs are available in a wide range. However, the main challenges faced are finding suitable donors, its expensiveness in the whole procedure, and the inability to perform on a large scale. In this commentary, summarization of the convalescent plasma therapy is done as a hopeful alternative therapy of severe or critical COVID 19. It has also emphasized the promising results shown since the past while the use of this therapy in various infectious diseases.